2016
DOI: 10.1038/srep30724
|View full text |Cite|
|
Sign up to set email alerts
|

Insight into the template effect of vesicles on the laccase-catalyzed oligomerization of N-phenyl-1,4-phenylenediamine from Raman spectroscopy and cyclic voltammetry measurements

Abstract: We report about the first Raman spectroscopy study of a vesicle-assisted enzyme-catalyzed oligomerization reaction. The aniline dimer N-phenyl-1,4-phenylenediamine (= p-aminodiphenylamine, PADPA) was oxidized and oligomerized with Trametes versicolor laccase and dissolved O2 in the presence of sodium bis(2-ethylhexyl)sulfosuccinate (AOT) vesicles (80–100 nm diameter) as templates. The conversion of PADPA into oligomeric products, poly(PADPA), was monitored during the reaction by in situ Raman spectroscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 61 publications
5
39
0
1
Order By: Relevance
“…ESI–MS measurements indicated that the extent of formation of unwanted oxygen-containing species during the early stages of PADPA polymerization is decreased in the presence of AOT vesicles (Junker et al 2014b). The conversion of PADPA into poly(PADPA) in the TvL/O 2 /AOT reaction system was also recently monitored during the reaction by in situ Raman spectroscopy which indicated, in accordance with complementary UV/Vis/NIR and EPR measurements, that at least some of the poly(PADPA) products resemble the conductive PANI emeraldine salt form (Janošević-Ležaić et al 2016). The Raman measurements showed that structural units different from those of “ordinary” PANI emeraldine salt are also present in poly(PADPA) (Janošević-Ležaić et al 2016).…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 76%
See 3 more Smart Citations
“…ESI–MS measurements indicated that the extent of formation of unwanted oxygen-containing species during the early stages of PADPA polymerization is decreased in the presence of AOT vesicles (Junker et al 2014b). The conversion of PADPA into poly(PADPA) in the TvL/O 2 /AOT reaction system was also recently monitored during the reaction by in situ Raman spectroscopy which indicated, in accordance with complementary UV/Vis/NIR and EPR measurements, that at least some of the poly(PADPA) products resemble the conductive PANI emeraldine salt form (Janošević-Ležaić et al 2016). The Raman measurements showed that structural units different from those of “ordinary” PANI emeraldine salt are also present in poly(PADPA) (Janošević-Ležaić et al 2016).…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 76%
“…The conversion of PADPA into poly(PADPA) in the TvL/O 2 /AOT reaction system was also recently monitored during the reaction by in situ Raman spectroscopy which indicated, in accordance with complementary UV/Vis/NIR and EPR measurements, that at least some of the poly(PADPA) products resemble the conductive PANI emeraldine salt form (Janošević-Ležaić et al 2016). The Raman measurements showed that structural units different from those of “ordinary” PANI emeraldine salt are also present in poly(PADPA) (Janošević-Ležaić et al 2016). It is important to note that PANI emeraldine salt-like poly(PADPA) products were not obtained in the PADPA/TvL/O 2 system without AOT vesicles.…”
Section: Enzymatic Polymerization Of Substituted Anilines and Other Amentioning
confidence: 76%
See 2 more Smart Citations
“…From a number of previous studies it has become clear that aqueous suspensions of anionic vesicles with a diameter of about 80-100 nm are suitable reaction media for the enzymatic oligo-or polymerization of aniline [1][2][3][4][5][6], the aniline dimer N-phenyl-1,4phenylenediamine (= p-aminodiphenylamine = PADPA; the trivial name is p-semidine) [7,8], or pyrrole [9]. With "suitable" we mean (i) that the presence of the vesicles as templates has a positive and desired influence on the outcome of the reaction with respect to the chemical structure of the products formed [10], (ii) that the reaction occurs with a high monomer conversion, and (iii) that no significant product precipitation is observed.…”
Section: Introductionmentioning
confidence: 99%